2004
DOI: 10.1097/01.ico.0000133997.07144.9e
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Association Between Signs and Symptoms in Patients With Dry Eye Disease

Abstract: These results suggest a poor relation between dry eye tests and symptoms, which represents a quandary in dry eye clinical research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
388
3
25

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 672 publications
(455 citation statements)
references
References 37 publications
24
388
3
25
Order By: Relevance
“…However, most studies do not mention which method was used in the tests (open or closed eyes) (16)(17)(18)(19)(20)(21) and there are no studies comparing both methods. Many authors have published their results using the test with closed eyes (4,(13)(14)(15) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies do not mention which method was used in the tests (open or closed eyes) (16)(17)(18)(19)(20)(21) and there are no studies comparing both methods. Many authors have published their results using the test with closed eyes (4,(13)(14)(15) .…”
Section: Methodsmentioning
confidence: 99%
“…Various authors have published articles using the test with the patients remaining with closed eyes (12)(13)(14)(15) , however, no study found evidence that such results are equivalents to the originally described tests by Schirmer. Recently, according to the 2007 Report of the International Dry Eye Workshop (DEWS), suggested to perform the Schirmer test with the patient's eyes closed (1) .…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, os resultados deste estudo demonstraram, na amostra estudada, fraca correlação entre os sintomas avaliados pelo questionário OSDI e os testes oculares. Estes resultados estão de acordo com os obtidos por outros autores que analisaram esta mesma correlação em formas diversas de olho seco desencadeados pela deficiência aquosa do filme lacrimal, incluindo síndrome de Sjögren (8)(9)(10)(11)14) .…”
Section: Discussionunclassified
“…Embora alguns autores tenham relatado casos de pacientes portadores da síndrome associados a intenso dano ocular, porém com ausência de sintomas (8,15) , não observamos na amostra estudada caso semelhante. Todos os pacientes deste estudo apresentavam índices do questionário OSDI superiores aos do grupo controle.…”
Section: Discussionunclassified
See 1 more Smart Citation